Trends in mortality from tuberculosis in England and Wales: effect of age on deaths from non-respiratory disease. Issue 9 (September 1995) - Doherty, M J; Spence, D P; Davies, P D
Abstract : BACKGROUND–Although mortality from tuberculosis has continued to fall in recent years, there has been little change in the case fatality rate for tuberculosis over the same period. This has previously been shown to be due to the increasing proportion of cases of tuberculosis occurring in the elderly. Tuberculosis mortality and case fatality were therefore analysed to determine if this disappointing trend in case fatality rate has occurred from disease in all or only certain sites. METHODS–A retrospective analysis of the tuberculosis mortality and case fatality rates in England and Wales for the period 1972-92 was carried out. The average annual percentage change in tuberculosis was calculated for each disease site and by age group and the results were compared. RESULTS–The analysis showed that, although the mortality rate fell steadily by 5.6% per annum, the case fatality rate decreased by only 0.9% (95% CI -1.7 to -0.1) per annum. The case fatality rate for respiratory and central nervous system disease declined, but no decline in tuberculosis at "other" sites was observed (1.01% (+2.2 to -0.2) for all age groups combined). In the group aged 75 and over, however, the proportion of deaths due to disease at other sites increased by 3.2% (2.2 to 4.3) per annum whilst in the other age groups the mortality rate declined. CONCLUSIONS–This analysis suggests that clinicians may be becoming less able to recognise non-respiratory presentations of tuberculosis, particularly in the elderly, and underlines the need to consider tuberculosis as a diagnosis to avoid delay in treatment.